Pengaruh Kecepatan Aliran Udara terhadap Dew Point Effectiveness (DPE) Pada Sistem Pendinginan Maisotsenko- Inderect Evaporative Cooling Non-Venturi Dengan Aliran Udara Horizontal Counter Flow - Pramagandi, I Komang Ake; Wijaksana, Hendra; Astawa, Ketut (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract This research aims to determine the effect of air flow speed on Dew Point Effectiveness (DPE) in the Maisotsenko- Inderect Evaporative Cooling Non-Venturi cooling system with horizontal Counter Flow air flow. Counter Flow means flow in the opposite direction, in the opposite direction is the working air flow from wet channel with primary air flow (product), in this M-Cycle system there are 2 dry channel and 1 wet channel, namely primary, secondary and wet channel. The air supply is directed to the dry channel in the primary and secondary channels, in the primary channel the air that comes out is product air for cooling and in the secondary channel the air is channeled to the wet channel through the passage between the secondary wall and the wet channel so that air enters from The secondary channel will enter the wet channel ans exit as working air. In this test, variation in air flow speed used were 5 m/s, 7 m/s, 9 m/s with a data collection time of 30 minutes and recorded every 5 minutes. Next, from each speed, look for the dew point effectiveness (DPE) value, which is a measure of the cooling system’s ability to cool the air to close to its condensation temperature. After testing, at speed of 5 m/s, 7 m/s, 9 m/s the dew point effectiveness was obtained at 21,5%, 22,9%, and 25%. Based on these result, it can be concluded that the highest dew point effectiveness is produced at an air flow speed of 9 m/s, namely 25% and the lowest at a speed of 5 m/s, namely 21,5%. Keywords : M-Cycle, Dew Point, Maisotsenko, Counter Flow, Wet Channel, Dry Channel